2016
DOI: 10.1097/coc.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Pazopanib and Ixabepilone in Patients With Solid Tumors

Abstract: The OTD for combination of pazopanib and ixabepilone was established. There was no impact of ixabepilone on pazopanib pharmacokinetics. The relationship between sE-selectin and progression free survival warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cell cycle arrest in S-phase is suggested to increase the susceptibility of tumors to etoposides and cisplatine, chemotherapeutics that are often administered to medulloblastoma patients [ 31 - 32 ]. Moreover, combinations of these chemotherapeutic agents with MKI have either been proven successful or are momentarily under investigation in clinical trials for other cancers [ 33 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest in S-phase is suggested to increase the susceptibility of tumors to etoposides and cisplatine, chemotherapeutics that are often administered to medulloblastoma patients [ 31 - 32 ]. Moreover, combinations of these chemotherapeutic agents with MKI have either been proven successful or are momentarily under investigation in clinical trials for other cancers [ 33 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A scientific rationale to combine ixabepilone with pazopanib in patients with uterine leiomyosarcoma may exist, as a recent Phase I study in patients with solid tumors reported at American Association for Cancer Research (AACR) in 2013 has defined a maximally tolerated dose of the combination with a high rate of disease stabilization [46]. Not surprisingly, the main toxicity was myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…They are a newer class of microtubuletargeting agents than taxanes. Numerous studies have confirmed the antitumor activity of epothilones in several tumor cell lines, even with high levels of P-glycoprotein (Ganesan et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 95%